2020
DOI: 10.1080/2162402x.2020.1800162
|View full text |Cite
|
Sign up to set email alerts
|

Anti-tumor immunity influences cancer cell reliance upon ATG7

Abstract: Macroautophagy (autophagy) is an essential cellular catabolic process required for survival under conditions of starvation. The role of autophagy in cancer is complex, context-dependent and at times contradictory, as it has been shown to inhibit, promote or be dispensable for tumor progression. In this study, we evaluated the contribution of the immune system to the reliance of tumors on autophagy by depleting autophagy-related 7 (ATG7) in murine tumor cells and grafting into immunocompetent versus immunodefic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Recent study indicated that loss of ATG7 in cancer cells which mediates autophagy disruption can enhance antitumor immune responses. 67 Our data suggest that ATG7 demethylation was closely associated with immune exclusion and CAF infiltration, which may provide insights into possible mechanisms.…”
Section: Discussionmentioning
confidence: 59%
“…Recent study indicated that loss of ATG7 in cancer cells which mediates autophagy disruption can enhance antitumor immune responses. 67 Our data suggest that ATG7 demethylation was closely associated with immune exclusion and CAF infiltration, which may provide insights into possible mechanisms.…”
Section: Discussionmentioning
confidence: 59%
“…In addition, conditions of “leaky gut” associated with the conditional ablation of Atg7 in epithelial colon cells predispose a local immune response that is instrumental for limiting the number of pre‐tumoral lesions in Apc + / − colonocytes (Levy et al , 2015 ). Consistently, CT26 cells knocked out for Atg7 show increased expression of chemokines involved in the recruitment of CD8 + T lymphocytes, and depletion of CD8 + T cells significantly restores the growth of tumors in immunocompetent hosts (Arensman et al , 2020 ).…”
Section: Cancermentioning
confidence: 84%
“…However, the drug resistance of glioma was not studied in this study, so whether DANCR can affect drug resistance by regulating ATG7-induced autophagy needs to be further studied. A recent study in mice showed that ATG7-related autophagy promoted anti-tumor immunity, thereby promoting tumor-cell survival (42). Hypoxia in glioma cells can induce intracellular protective autophagy, thus affecting glioma progression (43).…”
Section: Discussionmentioning
confidence: 99%